Tectonic soundscape: re-defining blindspots in public infrastructure (2023)
In a planet where resources are limited, nature collides with the impact of humankind.This proyect stems from the need to retrieve the sublimeness we find in nature and translate it into an architectural piece. The proyect is set in the Gilberto Echeverri Mejia Bridge in the city of Medellin. The existance of a vehicular bridge in an urban context generates a series of interrogations, the residual spaces on under and on the surroundings of the bridge become spaces with great opportunity for further intervention. Tectonic Soundscape is a programtically-varied cultural space where the sounds of nature converge with the artificial sounds created by the people of the city of Medellin and the machines that coexist within it. The light tectonic double-skin of the facade permits nature to enhabit the space, the sun to penetrate the steel-framed structure and the rain to fall in the large central cavity of the volcanic-like building.